THE INFLUENCE OF FINANCIAL LITERACY AND HEDONISTIC LIFESTYLE ON THE FINANCIAL BEHAVIOR OF GENERATION Z - Fajari, Hafizh; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study examines how financial knowledge and a hedonistic lifestyle affect Generation Z's financial behaviour. The term "Generation Z" describes those who were born between 1997 and 2012 and grew up in the information and technological age. Thirty-three members of Generation Z participated in the study in Malang. The research demonstrates how financial knowledge and a hedonistic lifestyle interact and influence Generation Z's financial behaviour. High financial literacy and the capacity to responsibly manage hedonistic lives are traits that Generation Z members have. The upshot is that it is crucial to create extensive financial literacy programs for Generation Z, taking the management of hedonistic lives into account. Programs that promote financial knowledge and education can aid Generation Z in developing healthier financial habits.